Discovering the anti-diabetic potential of pomegranate peel metabolites by examining molecular interplay with the thioredoxin-interacting protein - Aslam, Tahira; Arif, Amina; Arshad, Shafia; Muccee, Fatima; Ahmad, Khalil; Iqbal, Muhammad Omer; Khalil, Umair; Razak, Suhail; Afsar, Tayyaba; Almajwal, Ali; Shafique, Huma; Zain, Maryam (Frontiers in Medicine, 2024)
Introduction Medicinal plants like Punica granatum (pomegranate) have traditional uses against diabetes, inflammation and other diseases. The study was initiated to get an insight into the interaction tendency of P. granatum derived compounds with diabetes associated human thioredoxin-interacting protein (TXNIP). High glucose in diabetes induces production of TXNIP resulting in β-cells apoptosis. Its inhibition might reduce the diabetes incidence. Methods To elucidate the therapeutic potential of P. granatum peel against diabetes through GC-MS based identification of extracted compounds followed by application of computational algorithms. P. granatum peel extracts were screened for antioxidant, anti-inflammatory, anti-diabetic, antimicrobial and wound healing properties. Phytochemical and GC-MS based analysis were performed to identify the bioactive compounds. Molecular docking analysis was performed by Auto Dock Vina to predict the binding tendency of P. granatum derived compounds with TXNIP. Results and Discussion The peel exhibited antioxidant, anti-inflammatory and anti-diabetic activities, which were attributed to phytochemicals like phenols, tannins and steroids. GC-MS analysis identified 3,5-octadien-2-one, 1H-pyrrole -2,5-dione, Beta-D-lyxofuranoside, 5-O-(beta-D-lyxofuranosyl)-decyl, diethyl phthalate, 9-octadecenoic acid (Z)-, methyl ester, hexadecanoic acid, methyl ester, n-hexadecanoic acid, tetradecane, 2,6,10-trimethyl, bis (2-ethylhexyl) phthalate, decane, 3,8-dimethyl, 9-octadecenoic acid (Z)-, methyl ester and bis (2-ethylhexyl) phthalate in P. granatum peel extracts. Docking analysis revealed high binding affinities of bis (2-ethylhexyl) phthalate and 9-octadecenoic acid with TXNIP i.e., –4.5 and –5.0 kcal/mol, respectively, reflecting these compounds as potent antidiabetic agents. This study validates the traditional uses of P. granatum peel and demonstrates how computational approaches can uncover pharmacologically active phytochemicals. The results suggest P. granatum peel is a promising source of novel therapeutics against diabetes, inflammation, and oxidation. Further studies on the optimization of identified ligands are warranted.